2011
DOI: 10.1108/02610151111135769
|View full text |Cite
|
Sign up to set email alerts
|

From desegregation to diversity management in Alabama public universities: a narrative review

Abstract: PurposeThe purpose of the paper is to demonstrate that history has much to teach leaders in understanding resistance to affirmative action and how a greater commitment to diversity can be fostered.Design/methodology/approachThis narrative review provides a timeline of a case for resolution‐by‐agreement in the wake of the landmark Knight v. Alabama case.FindingsThere have been dramatic increases in the enrollment of students of color and the presence of African‐American faculty in the three major public univers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Since the Civil Rights movement of the 1960s, different strategies have been used to help discriminated groups of people gain equal access to opportunities regarding work, housing, healthcare, and education. During the 1970s and 1980s, passage and implementation of affirmative action, equal opportunity laws, and other nondiscriminatory policies assisted protected groups, based on race, gender, ethnicity, disability and other areas, to increase their representation in different areas of society and prevented future abuses (Edmondson, Dale, Feldman, & Yarber, 2011). These approaches were requirements in many cases and were enforceable via fines and other administrative penalties.…”
Section: Historical Backgroundmentioning
confidence: 99%
See 2 more Smart Citations
“…Since the Civil Rights movement of the 1960s, different strategies have been used to help discriminated groups of people gain equal access to opportunities regarding work, housing, healthcare, and education. During the 1970s and 1980s, passage and implementation of affirmative action, equal opportunity laws, and other nondiscriminatory policies assisted protected groups, based on race, gender, ethnicity, disability and other areas, to increase their representation in different areas of society and prevented future abuses (Edmondson, Dale, Feldman, & Yarber, 2011). These approaches were requirements in many cases and were enforceable via fines and other administrative penalties.…”
Section: Historical Backgroundmentioning
confidence: 99%
“…Affirmative Action. Edmondson et al (2011) examined the evolution of diversity management from affirmative action (AA) beginnings in higher education with a focus on the distinct differences between the legally mandated requirements of AA and the voluntary strategies of diversity management. This study found that advantages of diversity management include a position towards a systematic transformation of the organization instead of only recruitment and selection requirements usually found in AA regulations.…”
Section: Diversity Management To Inclusionmentioning
confidence: 99%
See 1 more Smart Citation